Organosomatic Indices and Histopathological Response of Clarias gariepinus Fed Black Cumin (Nigella sativa) Meal Diets - Kela, E; Sogbesan, A. O.; Michael, T. E.; Ishaku, A. H.; Muhammad, K. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2023)
The effects of different treated black cumin (Nigella sativa) meal diets on the organosomatic indices and histopathological response of organs of juvenile Clarias gariepinus was evaluated. The fish with initial mean weight and length: 9.94±0.02g and 10.08±0.04cm were stocked in triplicates per treatments. The fishes were fed experimental diets twice daily at 5% body weight, for 12 weeks. Six isonitrogenous diets containing 40% crude protein were formulated and coded as black cumin meal 1 (BCD Control), black cumin meal 2 (BCD2), black cumin meal 3 (BCD3), black cumin meal 4 (BCD4), and black cumin meal 5 (BCD5) respectively. Organosomatic indices such as cardiosomatic index (CSI), Hepatosomatic index (HSI), and Renalsomatic index (RSI) of the fish were measured using standard methods. Histopathological examinations of the liver, kidney and heart were carried out following routine laboratory techniques. Data were analyzed using descriptive statistics and ANOVA at á 0.05 level of significance. The result revealed a significant differences in all the orgaosomatic indices. The histopathological examinations of the liver of C. gariepinus revealed a gradual changes from mild to moderate and severe diffuse hepatic vacuolar degenerations as the concentrations of black cumin meal diets increased. The study revealed that the consumption of black cumin does not have negative implication and improved growth performance of the fish.